Walking a tightrope: Christians and Muslims in post-genocide Rwanda - Kubai, Anne (Islam and Christian-Muslim relations, 2007)
The 1994 genocide has become a major factor in Rwandan history. At its root lie both ethnic and religious dimensions. These events are considered in the context of a long history of tension and conflict between segments of the population. Religion having contributed to the radicalization of social identities through the involvement of the religious leadership in the genocide, the article analyses Christian–Muslim relations in post-genocide Rwanda. Interviews with Christians and Muslims show that the hitherto marginalized Muslim minority has been able to protect victims and, in cooperation with other groups, has embarked on jihād to enhance and facilitate reconciliation. As a result, both Tutsis and Hutus have been turning to Islam.